Innovative Methods of Teaching English and Methods of Using Them - Valiqul o'g'li, Kataev Salakhiddin (European Journal of Life Safety and Stability (2660-9630), 2021)
At present, special attention is paid to the teaching of foreign languages in our country. These include English and its teaching methods. This article discusses English language teaching, its methodology, as well as innovative teaching methods currently being taught